BIOKUAGULAN DARI LIMBAH KULIT UDANG UNTUK PENJERNIHAN AIR LIMBAH PERKOTAAN - Sari, Alvika Meta; Setiawan, Eko; Ali, Danang (Jurnal Teknologi, 2012)
ABSTRACT. The objective of this study is to prepare biocoagulant from shrimp waste for municipal wastewater treatment. Shrimp waste was ground and deproteinized using NaOH solution at 100 ÃÂºC for 2 hours, then demineralized using HCl at 80 ÃÂºC for 8 hours to form chitin. The chitin was then deacetylized by NaOH solution at varied temperatures of 60-70 ÃÂºC for 4 hours of heating to form chitosan. The chitosan was then used as a biocoagulant for municipal wastewater. This study refers to jar test results, where there were parametersto be assessed, such as turbidity decrease (NTU), reduction in heavy metals levels compared to those prior to chitosan addition, pH influence on coagulation, and optimum concentration used as compared to the use of aluminium sulfate. This study revealed that pH 7 was the optimum condition.